Identification of genes with altered expression in male and female Schlager hypertensive mice - Chiu, Christine L (BMC Med Genet, 2014)
BACKGROUND: Numerous studies have shown sex differences in the onset and severity of hypertension. Despite these sex-differences the majority of animal studies are carried out in males. This study investigated expression changes in both male and female hypertensive mouse kidneys to identify common mechanisms that may be involved in the development of hypertension. METHODS: The Schlager hypertensive mouse model (BPH/2J) and its normotensive control (BPN/3J) were used in this study. Radiotelemetry was performed on 12 to 13 week old BPH/2J and BPN/3J male and female animals. Affymetrix GeneChip Mouse Gene 1.0 ST Arrays were performed in kidney tissue from 12 week old BPH/2J and BPN/3J male and female mice (n = 6/group). Genes that were differentially expressed in both male and female datasets were validated using qPCR. RESULTS: Systolic arterial pressure and heart rate was significantly higher in BPH/2J mice compared with BPN/3J mice in both males and females. Microarray analysis identified 153 differentially expressed genes that were common between males and females (70 upregulated and 83 downregulated). We validated 15 genes by qPCR. Genes involved in sympathetic activity (Hdc, Cndp2), vascular ageing (Edn3), and telomere maintenance (Mcm6) were identified as being differentially expressed between BPH/2J and BPN/3J comparisons. Many of these genes also exhibited expression differences between males and females within a strain. CONCLUSIONS: This study utilised data from both male and female animals to identify a number of genes that may be involved in the development of hypertension. We show that female data can be used to refine candidate genes and pathways, as well as highlight potential mechanisms to explain the differences in prevalence and severity of disease between men and women. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12881-014-0101-x) contains supplementary material, which is available to authorized users.